Sample acceptance time criteria, electronic issue and alloimmunisation in thalassaemia. Issue 6 (23rd November 2015) - Trompeter, S.; Baxter, L.; McBrearty, M.; Zatkya, E.; Porter, J.
SUMMARY: Objectives: To determine the safety of a 1‐week acceptance criteria of sample receipt in laboratory to transfusion commencement in transfusion dependent thalassaemia with respect to alloimmunisation. To determine the safety of electronic issue of blood components in such a setting. Methods: Retrospective audit of alloimmunisation (1999–2012) and blood exposure in registered thalassaemia patients at a central London thalassaemia centre where the acceptance criteria for the group and save sample from arrival in the laboratory to the time of issue of blood for transfusion for someone who has been transfused in the last 28 days was 1 week, and there was electronic issue protocol for patients who have always had a negative antibody screen (other than temporary positivity in pregnant women receiving prophylactic anti‐D or anti Le‐a, Anti Le‐b and Anti P1 that are no longer detectable). Results: There were 133 patients with thalassemia variants regularly attending UCLH for review. A total of 105 patients had transfusion dependent thalassaemia (TDT) (7 E‐beta thalassaemia, 98 beta thalassaemia major). Ten of the 84 patients who received their transfusions at UCLH were alloimmunised. Seven of them had been alloimmunised prior to arrival at UCLH. Only two patients developed antibodies at UCLH during this period. Conclusion: The prevalence of alloantibody formation of 2% in UCLH transfused patients, with presumptive incidence of 0·01 alloantibodies per 100 units or 0·001 immunisations per person per year compares favourably with other reported series and suggests that 1 week interval with appropriate electronic issue is acceptable practice.